Long‐term heavy reindeer grazing promotes plant phosphorus limitation in arctic tundra. (29th April 2019) - Sitters, Judith; Cherif, Mehdi; Egelkraut, Dagmar; Giesler, Reiner; Olofsson, Johan
Abstract: The potential of large mammalian herbivores to shift plant communities between nitrogen (N) and phosphorus (P) limitation has received little attention so far. However, herbivores can influence the cycling of these growth‐limiting nutrients, and thereby affect plant nutrient limitation and productivity. Tundra ecosystems are nutrient‐poor and commonly grazed by large herbivores like reindeer and may thus be responsive to such changes. Here, we examined the effect of long‐term light and heavy reindeer grazing on nutrient limitation of plant growth in a Scandinavian arctic tundra. We are the first to conduct a factorial N and P fertilization experiment across the two grazing regimes in two functionally contrasting vegetation types: heath and meadow. Annual primary productivity (APP) showed contrasting responses to our fertilization treatments under light and heavy grazing. Under light grazing, APP increased in response to N + P additions in both the heath and meadow. Under heavy grazing, APP increased in response to N in the heath, with an additional positive effect of N + P combined, while APP increased in response to P and N + P additions in the meadow. These results clearly show that an increase in the grazing intensity of reindeer facilitated a shift towards more P‐limited conditions in Scandinavian arctic tundra, by increasing N cycling without having a corresponding positive effect on P cycling. In the N‐poor heath, reindeer increased soil N availability at least partly due to a shift towards more N‐rich graminoids, while in the meadow, reindeer decreased soil P availability. The mechanisms behind this decrease remain unclear, but reindeer may simply export more P from the system than N due to their large P demand for the production of their antlers. Synthesis . We conclude that heavy and long‐term reindeer grazing promoted a more P‐limited tundra, thus experimentally confirming the potential of large mammalian herbivores to influence nutrient limitation of plant growth. A plain language summary is available for this article. Abstract : Plain Language Summary